SYNTHESIS OF DEOXYNOJIRIMYCIN AND OF NOJIRIMYCIN DELTA-LACTAM - Fleet, G; Carpenter, N; Petursson, S; Ramsden, N (1990)
The syntheses of nojirimycin δ-1actam and of deoxynojirimycin from a divergent ido-furanose intermediate are reported. © 1990.